In vitro study on the antimicrobial activities of Orgacids™ against some important bacteria - Zakaria, Zunita; Goh, Yong Meng; Selamat, Mohd Hajaraih; Norshidin, Mohd Jefri; Hassan, Latiffah; Ang, S. K. (Universiti Putra Malaysia Press, 2004)
OrgacidsTM is an unique acidifier containing balanced amount of formic, phosphoric, lactic, tartaric, citric and malic acids. It is recommended for use in poultry feeds for the improvement of host health as it is able to inhibit pathogenic bacteria in animal feeds and in the gastrointestinal tract. A study was carried out to determine the antimicrobial activities of OrgacidsTM against 21 Gram positive and Gram negative bacteria using the broth method. The results obtained showed that OrgacidsTM at the concentration of 0.20% was effective in inhibiting the growth of most bacteria tested.